Etnobotany in the Ejido Pablillo, Galeana, Nuevo Leon, Mexico - Estrada-Castillón, Eduardo; Virgen-Flores, Monserrat; Himmlesbach, Wibke; Sanchez Salas, Jaime; García Aranda, Mario Alberto; Valdes Alameda, Renata Aide (Ecosistemas y Recursos Agropecuarios, 2025)
A study of useful plants in the Ejido Pablillo, Galeana, Nuevo Leon, Mexico was carried out. One hundred semi-structured surveys were conducted (18 men and 82 women) to gather information on the plant species used and the uses they give them in their daily lives. Two quantitative ethnobotanical indices were analyzed, the Consensus Factor Index (FIC) and the Value of Use Index (IVU) to evaluate the importance of the species within the ejido community. Seventy-three families, 156 genera and 203 species of plants were recorded. The main uses were ornamental with 61 families, 100 genera and 122 species, followed by food plants (22 families, 43 genera and 54 species) and medicinal plants (22 families, 37 genera and 38 species). Other important uses were wood, fuel, and construction. The FIC showed that although there is no broad consensus on the use of medicinal species used, since their use varies among most of them, the UVI species, there are some that are traditionally important and used to cure certain ailments.